Manajemen Ekonomi Islam dalam Strategi Green Economy Berbasis Daur Ulang Limbah - Suci Dianthiny (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze Islamic economic management in a Green Economy Strategy Based on Waste Recycling. Currently, the increasing environmental problems faced by current and future generations have focused much attention on environmental protection and the growth of sustainable development. These environmental problems are not the responsibility of individuals or governments alone, but are something that needs to be addressed together. Green economy in this study is the management of waste such as mud, wood, clothing, plastic that can be utilized as entrepreneurship to restore the economy of affected communities. In addition, the integration of Islamic management and economics in a Green Economy Strategy based on flood waste recycling in this affected area can help the government in dealing with waste and in accordance with the concept of maqashid sharia. This study uses a qualitative approach with a descriptive-analytical method and is enriched with a case study approach in disaster-affected areas. The results of this study enrich the study of Islamic economics by incorporating the perspective of the green economy and environmental management as an integral part of the Islamic economic system. This research demonstrates that Islamic economics is relevant and adaptive in addressing the challenges of the environmental crisis and sustainable development. The findings can serve as a basis for local governments, Islamic financial institutions, and MSMEs in designing green economy-based waste management policies and programs that align with Islamic values.